Health inequities among persons with disabilities: a global scoping review - Emre Umucu; Andrew A. Vernon; Deyu Pan; Sang Qin; Guillermina Solis; Rebecca Campa; Beatrice Lee (Frontiers in Public Health)
Background and objectiveApproximately 16% of the global population, or 1.3 billion individuals, live with disabilities, facing increased health risks. Despite international and national policies affirming the rights of persons with disabilities, healthcare disparities persist, with studies revealing higher rates of unmet medical needs, avoidable deaths, and dissatisfaction with healthcare services among this population. This scoping review aims to provide a comprehensive overview of health inequities experienced by individuals with disabilities globally.MethodsA rapid scoping review methodology was employed to systematically search and analyze quantitative evidence on health inequities. Electronic searches were conducted in CINAHL, MEDLINE, and PsycINFO databases, supplemented by manual searches of reference lists. The selection criteria for articles in this study were as follows: (a) publication between 2011 and 2022, (b) written in English, (c) published in a peer-reviewed scholarly journal, and (d) a quantitative comparison of health inequities between persons with and without disabilities.ResultsA total of 363 scholarly works were initially identified, with 51 meeting the inclusion criteria after rigorous screening. In the course of our review, our team identified three overarching themes of health inequity, encompassing (a) access to healthcare and resources, (b) morbidity, mortality, & risk factors, and (c) social determinants of health. These studies collectively reveal disparities in healthcare access, utilization, and outcomes among persons with disabilities, highlighting the urgent need for targeted interventions to address systemic barriers and promote equitable healthcare provision.ConclusionThis review underscores the challenges faced by individuals with disabilities in accessing quality healthcare and imperative for concerted efforts to advance health equity.